2014
DOI: 10.1002/app.40908
|View full text |Cite
|
Sign up to set email alerts
|

Robust polymeric hydrogel using rod‐like amidodiol as crosslinker: Studies on adsorption kinetics and mechanism using dyes as adsorbate

Abstract: Herein, we report the preparation of robust polyacrylic acid hydrogel using rod-like amidodiol as physical crosslinker. Polyacrylic acid-amidodiol hydrogels were characterized for its chemical structure, rheology, swelling, diffusion, and adsorption properties. Kinetics and mechanism of adsorption were investigated by UV-visible spectroscopy using dyes such as rhodamine 6G and methylene blue as adsorbate. Results suggested pseudo second-order kinetics of multilayer adsorption and hydrogel could retain its shap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…17 The chelation is some kind of chemical interaction, which is apparently stronger than physical adsorption between inorganic carrier and metal ions. Besides, it has been reported that silica−chitosan hybrid materials exhibit an enhanced mechanical property compared with other hybrid materials because of addition of silica, 18,19 so the silica/chitosan hybrid material is a good choice of support for noble metal nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…17 The chelation is some kind of chemical interaction, which is apparently stronger than physical adsorption between inorganic carrier and metal ions. Besides, it has been reported that silica−chitosan hybrid materials exhibit an enhanced mechanical property compared with other hybrid materials because of addition of silica, 18,19 so the silica/chitosan hybrid material is a good choice of support for noble metal nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…This was observed even for high values of 1/n, which can reach about ten (between 2 and 12) (Gu and Zhu 1990, Yurdakoç, Seki et al 2005, Khandelwal, Narayanan et al 2020. This correspondence can be attributed, at low concentrations, to the difference between the force of diffusionswelling of solvent versus the force of concentration gradient and mass transfer of solute (Kaşgöz and Durmus 2008, Narayanan, Nethran et al 2014, Bai, Zhang et al 2016, Du and Piao 2018, Saraydın, Işıkver et al 2018.…”
Section: Adsorption Isothermsmentioning
confidence: 87%
“…Gile's plot showed that 1 gram of Dext-g-poly(AMPS-co-AA) polymer can adsorb upto 164 mg of dimethoate, 149 mg of phosalone, and 136 mg of chlorpyrifos. [76,77] 3.12 | Thermodynamic parameters Adsorption thermodynamic parameters, namely Gibbs free energy change (ΔG O Þ, enthalpy change ΔH O À Á , and entropy change (ΔS O Þ for the adsorption of studied pesticides onto the polymer are calculated using the following Van't Hoff equation:…”
Section: Nature Of Adsorption Isotherm Using Gile's Modelmentioning
confidence: 99%